Prolonged continuous infraclavicular brachial plexus perineural infusion following replantation of a mid-humeral amputation - Sean P Clifford; Brittany D Maggard; Kelly M Hines (SAGE Open Medical Case Reports, 2019)
Replantation of a traumatic upper extremity amputation is a complex process accompanied by prolonged hospitalization, extended rehabilitation, and potential for graft failure secondary to poor perfusion to the distal extremity. The patient is faced with repeat visits to the operating room in addition to severe acute and chronic pain issues. We present the case of an 18-year-old male treated with prolonged continuous peripheral nerve blockade following traumatic left mid-humeral amputation and subsequent replantation. The patient maintained infraclavicular brachial plexus catheterization until hospital discharge, a course spanning 33 days and six follow-up surgical procedures. The patient was pain free and had been weaned off all opioids at a 4-week outpatient surgical debridement. Prolonged continuous infraclavicular brachial plexus blockade following replantation surgery has numerous potential benefits including augmentation of perfusion to the injured extremity, management of severe acute post-traumatic pain, and prevention of the chronic pain associated with transected nerves.